Altered cingulate and insular cortex activation during risk‐taking in methamphetamine dependence: losses lose impact. (24th October 2013) - Gowin, Joshua L.; Stewart, Jennifer L.; May, April C.; Ball, Tali M.; Wittmann, Marc; Tapert, Susan F.; Paulus, Martin P.
Abstract Aims To determine if methamphetamine‐dependent (MD) individuals exhibit behavioral or neural processing differences in risk‐taking relative to healthy comparison participants (CTL). Design This was a cross‐sectional study comparing two groups' behavior on a risk‐taking task and neural processing as assessed using functional magnetic resonance imaging (fMRI). Settings The study was conducted in an in‐patient treatment center and a research fMRI facility in the United States. Participants Sixty‐eight recently abstinent MD individuals recruited from a treatment program and 40 CTL recruited from the community completed the study. Measurements The study assessed risk‐taking behavior (overall and post‐loss) using the Risky Gains Task (RGT), sensation‐seeking, impulsivity and blood–oxygenation‐level‐dependent activation in the brain during the decision phase of the RGT. Findings Relative to CTL, MD displayed decreased activation in the bilateral rostral anterior cingulate cortex (ACC) and greater activation in the left insula across risky and safe decisions (P < 0.05). Right mid‐insula activation among CTL did not vary between risky and safe decisions, but among MD it was higher during risky relative to safe decisions (P < 0.05). Among MD, lower activation in the right rostral ACC (r = −0.39, P < 0.01) and higher activation in the right mid‐insula (r = 0.35, P < 0.01) during risky decisions were linked to a higher likelihood of choosing a risky option following a loss. Conclusions Methamphetamine‐dependent individuals show disrupted risk‐related processing in both anterior cingulate and insula, brain areas that have been implicated in cognitive control and interoceptive processing. Attenuated neural processing of risky options may lead to risk‐taking despite experiencing negative consequences.